Comparability of questionnaires - Landers, Alynne; McNiff, Melissa (DHS Methodological Reports No. 4, 1994)
This report documents the contents of questionnaire s used in 27 surveys conducted under Phase 1 of the Demographic and Health Surveys Programs. The report consists of a collection of tables containing information on the inclusion and wording of questions and their deviations from the Model "A" and Model "B" (or core) questionnaires. The tables are intended to be useful to those carrying out analyses, especially comparative analyses, of DHS data files. A description of each set of tables is provided below. It is important for users of this report to be aware, however, that while tables shown here provide information on the contents of the questionnaires used in surveys, there is no substitute for examining the questionnaires themselves. Country-specific questionnaires can be found in the final report of each survey.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The Demographic and Health Surveys (DHS) is a 13-year project to assist government and private agencies in developing countries to conduct national sample surveys on population and maternal and child health. Funded primarily by the United States Agency for International Development (USAID), DHS is administered by Macro International Inc. in Calverton, Maryland, USA.